A Study on the Relationship Between Career Advancements, Job Characteristics, Job Satisfaction and Employee Commitment in the Healthcare Industry (Architecture Image Studies, 2025)
Healthcare systems face rural–urban workforce imbalances and efficiency gaps. Knowledge-sharing among clinicians is a key lever to improve service quality. Drawing on Social Exchange Theory, this study examines how career advancement (CA) opportunities and job characteristics (JC) influence knowledge-sharing behavior (KSB), and whether subjective norms (SN) amplify these effects. A cross-sectional survey was conducted in 2019 among healthcare professionals from eight public hospitals in Laos. Of 450 questionnaires distributed, 310 valid responses were obtained (68% response rate). Respondents were mainly nurses (71%) and doctors (29%), with most aged 21–30 years. Validated scales measured CA, JC, SN, and KSB on a five-point Likert scale. Data was analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to test reliability, validity, and hypothesized relationships. All constructs showed strong reliability (CR = 0.85–0.91) and validity (AVE = 0.53–0.70). Structural analysis confirmed positive effects of CA (β = 0.189, p < 0.05), JC (β = 0.272, p < 0.01), and SN (β = 0.416, p < 0.01) on KSB. Mediation tests showed that SN strengthened the effects of CA (β = 0.232, p < 0.01) and JC (β = 0.376, p < 0.01) on knowledge-sharing. Findings highlight that supportive job design, clear career pathways, and organizational norms foster knowledge-sharing among healthcare staff. Both CA and JC directly and indirectly (via SN) promote KSB. Administrators should prioritize structured career development, supportive job design, and norm-building initiatives such as leadership endorsement and peer recognition. Future research should explore these relationships in varied contexts and test demographic moderators to enhance generalizability.